2011
DOI: 10.1007/bf03326243
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid fatty acids analysis of the vertical distribution of microbial communities in eutrophic lake sediments

Abstract: Vertical distribution of microbial communities in a eutrophic lake sediments of Lake Xuanwu was quantified by phospholipid fatty acids analysis and multivariate statistical analysis was employed to interprete the data. Principle component analysis of sediment characteristics parameters, including total nitrogen, total phosphorus, organic matters and pH produced clustering of sampling sites for two distinct groups. These groups corresponded with the two sampling stations and the levels of nutrient enrichment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…So far, the diversity and structure of bacterial community in lake sediment have been extensively investigated. Lake sediment bacterial community can be shaped by a variety of environmental factors, such as sediment depth (Nam et al 2008;Shivaji et al 2011;Villaescusa et al 2011), salinity (Dai et al 2013;Jiang et al 2007;Swan et al 2010), phosphorus (Song et al 2012;Zeng et al 2009), organic matter (Bai et al 2012;Zeng et al 2009), pH (Zeng et al 2009;Zhao et al 2011), and pollution (Haller et al 2011). These results were obtained based on the interlake investigations.…”
Section: Introductionmentioning
confidence: 77%
“…So far, the diversity and structure of bacterial community in lake sediment have been extensively investigated. Lake sediment bacterial community can be shaped by a variety of environmental factors, such as sediment depth (Nam et al 2008;Shivaji et al 2011;Villaescusa et al 2011), salinity (Dai et al 2013;Jiang et al 2007;Swan et al 2010), phosphorus (Song et al 2012;Zeng et al 2009), organic matter (Bai et al 2012;Zeng et al 2009), pH (Zeng et al 2009;Zhao et al 2011), and pollution (Haller et al 2011). These results were obtained based on the interlake investigations.…”
Section: Introductionmentioning
confidence: 77%
“…Thus, the microbial composition of alpine lake sediments is affected. Sediment SWC (Guo et al., ), pH (Zhao et al., ), DO (Yadav, Khardenavis, & Kapley, ), depth (Zhang et al., ), and geographic factors such as altitude (Chen et al., ) can also influence the composition of microbial communities. From the sample–environment relationship (Figure b) we found that the two groups that are geographically close (DK, WD‐2, and ZN; NB‐1 and SL) are distributed far apart in the figure.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the microbial composition of alpine lake sediments is affected. Sediment SWC (Guo et al, 2015), pH (Zhao et al, 2011), DO (Yadav, Khardenavis, & Kapley, 2014), depth ,…”
Section: The Relationship Between the Microbial Community And Envirmentioning
confidence: 99%
“…The initial detrended correspondence analysis (DCA) results demonstrated that the data exhibited linear rather than unimodal response to the environmental variables (most gradient lengths were 0.224, < 2) [48][49][50], so RDA was performed to explain the data by CANOCO 4.5 (Biometris, Wageningen, Netherlands) [45][46]. Ordination biplots including phospholipid fatty acid composition and environmental variables were used to explain the data.…”
Section: Multivariable Statistics Analysismentioning
confidence: 99%